MONITORING KONDISI TANAH DAN RUANGAN PADA PROTOTYPE GREEENHOUSE BIBIT KENTANG BERBASIS MIKROKONTROLLER DAN HMI NEXTION - Sjahrul, Yurika; Setiana, Randi Febri (Jurnal TEDC, 2024)
The use of greenhouses can be an alternative in cultivating potato seeds with room conditions that can be manipulated according to plant needs. The greenhouse system can provide a solution for farmers because it can work automatically and can be monitored via HMI. This system can also perform the function of controlling room temperature and humidity, soil humidity, and soil pH according to the conditions around the greenhouse. The monitoring and data collection process includes data on room temperature and humidity sensor readings by maintaining the temperature below 24 ℃ with ambient humidity above 60%. Based on the results of monitoring soil pH and soil moisture, data was obtained that the system would maintain soil conditions with a pH value of 7.00 and humidity of 60%. The use of RTC in the pesticide spraying process is carried out in real time in the morning at 08.00 and afternoon at 17.00. The use of HMI as an interface for delivering sensor value data is very helpful for users or authors in the monitoring process and data collection.